Investigating the use of polymer-modified cementitious thin spray-on liners as stope face support. (June 2021) - du Plessis, M.; Malan, D.F.
Abstract: This paper investigates the use of a thin spray-on liner (TSL) as stope face support in narrow width tabular stopes. The application of areal support is difficult in these stopes because of the small stoping width and the large area of hanging wall that is exposed by the long face lengths and regular blasting. A simple analytical model of a collapsing block supported by a TSL is explored to determine the parameters to be considered for underground use of the liners. Most literature on TSL focusses mostly on specialised laboratory testing. Almost no large scale testing to determine TSL strengths, when it is applied to blocky rock masses, has been conducted. To simulate the discontinuous nature of the hanging wall in mining stopes, a large scale rig and test methodology was developed. Four different polymer-modified cementitious TSL products were tested and the results are described in the paper. For the particular experimental setup and a curing time of 24 h, the maximum load carrying capacity of the strongest TSL was 305 kg, while a 50 mm thick shotcrete had a capacity exceeding 1100 kg. The test results indicate that care should be exercised when attempting to use a TSL as a structural element in support systems.